The effects of methyl donor supply and methyl group status on growth performance, health, and methionine metabolism in growing cattle - Grant, Madeline Sue (Kansas State University, 2024)
Three experiments were conducted to evaluate the effects of supplemental methyl group donors in growing cattle. In a 3-year experiment, 1440 crossbred beef heifers (480 per year; 224 kg initial body weight) were utilized to study the effects of methionine (Met) or choline supplementation on high-risk receiving cattle. Heifers were limit-fed at 2.2% of body weight daily a corn- and corn-coproduct-based diet for 60 d and supplemented with 1 of 5 treatments: control (nothing), 5 g/d metabolizable Met (8.33 g/d Smartamine M), 15 g/d metabolizable Met (25 g/d Smartamine M), 1.17 g/d available choline (26 g/d Reashure), or 3.5 g/d available choline (78 g/d ReaShure). Treatments were top-dressed at feeding daily. Jugular blood samples were collected on d 0, 14, and 60. Plasma haptoglobin was measured to assess inflammation and plasma antioxidant potential (AOP) was measured to assess oxidative balance. Dry matter intake was not affected by treatment (P ≤ 0.25). Some minor differences among treatments were observed for body weight, average daily gain, and gain:feed throughout the experiment; however, none of the treatments differed from control. Overall prevalence of respiratory morbidity and mortality were 29% and 0.69%, respectively. No treatment effects were detected for first, second, or third respiratory morbidity or mortality (P ≥ 0.30). Plasma haptoglobin was lesser for on d 14 for 1.17 g/d than for control, 5 g/d Met, and 3.5 g/d choline (P ≤ 0.01) and tended to be lesser than 15 g/d Met (P = 0.06); plasma haptoglobin did not differ among treatments on d 0 or d 60 (P > 0.51). Plasma antioxidant potential (AOP) was not affected by dietary treatment (P = 0.53). Overall, supplemental Met and choline did not affect growth performance or health; however, choline supplementation may decrease inflammation in high-risk, newly received heifers. Two experiments were conducted using ruminally cannulated Holstein steers (Exp. 1, n=7, 189 kg; Exp. 2, n=6, 161 kg) in 6×6 Latin square designs with 10-d periods. Factorial treatments were continuously infused abomasally and included 3 methyl group modulators (MGM; Exp. 1&2: control; 15 g/d guanidinoacetic acid [GAA]; or 16.8 g/d creatine) and 2 levels of betaine (Exp.1; 0 or 5.7 g/d betaine) or 2 levels of Met (Exp. 2; 0 or 7.2 g/d Met). Supplemental GAA or creatine increases creatine supply, but GAA consumes methyl groups during conversion to creatine, whereas creatine spares methyl groups by reducing GAA synthesis. Steers in both experiments were fed 3.5 kg/d (DM basis) of a corn-based diet. On d 10 of each period, whole-body Met flux was measured by continuous jugular infusion of 1-¹³C-L-Met and methyl-²H₃-L-Met. Retained N was not affected by MGM in either experiment (P ≥ 0.63). In both experiments, supplemental GAA increased plasma concentrations and urinary excretion of GAA and creatine (P < 0.01), whereas supplemental creatine only increased plasma concentrations and urinary excretion of creatine (P < 0.01). Supplemental GAA numerically increased use of Met for methylation reactions and remethylation of homocysteine to regenerate Met; as a result, GAA did not affect irreversible loss of Met via transsulfuration. In Exp. 1, Plasma haptoglobin decreased numerically with GAA but increased numerically with creatine; plasma haptoglobin was not affected by treatment in Exp. 2. Supplemental betaine, but not Met, increased retained N (P = 0.03). Supplemental Met, but not betaine, increased urinary creatine excretion (P = 0.02). Supplemental Met, GAA, and creatine tended to decrease lipopolysaccharide (LPS)-challenged neutrophil phagocytosis; betaine did not affect phagocytosis in LPS-challenged neutrophils (P = 0.89). Overall, our data suggest that our cattle were not deficient in available methyl groups, even when GAA was provided as a methyl group consumer, and effects of Met, creatine, and GAA on inflammation and immune function were likely not a result of changes in methyl group status.
Keywords: Methyl group; Methionine; Choline; Betaine; Guanidinoacetic acid; Cattle